Цифрове сільське господарство: досвід України - Деркач, Олексій Дмитрович; Derkach, Oleksii; Михайліченко, Євген Миколайович; Mykhaylichenko Yevhen, Yevhen; Макаренко, Дмитро Олександрович; Makarenko, Dmytro (Scientific Technical Union of Mechanical Engineering "Industry 4.0", 2021)
Реалізується освітній проект з підготовки студентів у галузі цифрових технологій для сільського господарства. Проект був реалізований у Дніпровському державному аграрно-економічному університеті. Обладнання надало ТОВ «АгроКМР”. Наведено огляд програмного забезпечення вітчизняного та зарубіжного виробництва, що працює в галузі цифрового сільського господарства. Розглянуто переваги використання цифрового сільського господарства. Як приклад, реалізація функцій диференційованого сівби соняшнику агрегатом Case IH Magnum 380 + Horsch Maestro 36.50SW, для якого розроблені студентами карти сівби. Посів був виконаний в реальних умовах. Показано, що фермери та власники агрохолдингів повинні бути більше зацікавлені у функціонуванні такого проекту, ніж університети – адже це суттєво оптимізує та автоматизує виробництво. Без таких технологій у найближчі роки сільськогосподарські підприємства почнуть втрачати конкурентоспроможність. For example of the implementation of an educational project to train students in the field of digital agriculture technologies is given. The project was implemented at the Dnipro State Agrarian and Economic University. The equipment was provided by LLC “Agro KMR” for information. An overview of software of Ukrainian and foreign production working in the field of digital agriculture is given. The advantages of using digital agriculture are shown. As an example, the implementation of the functions of differentiated sowing of sunflower by the unit Case IH Magnum 380 + Horsch Maestro 36.50SW, for which sowing maps were developed by students, is given. Sowing was performed in real conditions. It is shown that farmers and owners of agricultural holdings should be more interested in the functioning of such a project than universities - because it significantly optimizes and automates production. Without such technologies in the coming years, agricultural enterprises will begin to lose competitiveness.
Digital agriculture: the experience of Ukraine
Keywords: цифрове сільське господарство; Digital farming; сільське господарство; agricultural; обладнання; equipment; навчання; study